The role of interactive digital content in developing learners’ competence in the Arabic language - ghilous, salah; refis, belkhir (El Omda in Linguistics and Discourse Analysis, 2025)
The remarkable qualitative leaps in the fields of information and communication technology and the Internet, and the accompanying digital transformation, as well as the use and integration of information technology in the educational system, which leads to the spread of a culture of self-learning and cooperative learning through interactive digital content for language learning, which motivates learners to pay attention and focus, and contribute to improving their performance and cognitive achievement, through the use of positive interaction techniques and participation in innovative experiences. And contribute to improving the effectiveness of their performance and cognitive achievement, through the use of positive interaction techniques and active participation in creative and critical learning. Audio-visual aids such as : Computers and interactive videos reduce the excessive use of direct instruction. The use of interactive digital content for teaching and learning the Arabic language is an effective way to attract, engage, and directly interact with learners, using techniques of positive interaction and participation in an innovative and exciting experience.